2022
DOI: 10.1021/acsmaterialslett.2c00075
|View full text |Cite
|
Sign up to set email alerts
|

Bimetal Biomimetic Engineering Utilizing Metal–Organic Frameworks for Superoxide Dismutase Mimic

Abstract: In the past decade, scientists sought to engineer nanomaterials with natural enzymes-like biological function, and searched for newfangled applications. Herein, we show the first example of utilizing a bimetal metal–organic framework (MOF-818) platform for mimicking of Cu/Zn-superoxide dismutase (Cu/Zn-SOD), an important antioxidant enzyme that specifically scavenges superoxide anions. Experimental data and theoretical calculations reveal that the high Cu/Zn-SOD-like activity of MOF-818 results from the bimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…In the high-resolution N 1s spectrum, the peak at 399.4 eV demonstrated the existence of the N–Cu bond and the binding energy peak at 401.9 eV was assigned to R-NH 2 in MOF-818/PDA (Figure S1B). In the Zr 3d spectrum, the 3d 3/2 and 3d 5/2 states correspond to 182.7 and 185.2 eV, respectively (Figure S1D), demonstrating the presence of Zr 4+ in MOF-818. The X-ray diffraction (XRD) patterns of MOF-818 are shown in Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…In the high-resolution N 1s spectrum, the peak at 399.4 eV demonstrated the existence of the N–Cu bond and the binding energy peak at 401.9 eV was assigned to R-NH 2 in MOF-818/PDA (Figure S1B). In the Zr 3d spectrum, the 3d 3/2 and 3d 5/2 states correspond to 182.7 and 185.2 eV, respectively (Figure S1D), demonstrating the presence of Zr 4+ in MOF-818. The X-ray diffraction (XRD) patterns of MOF-818 are shown in Figure S3.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of M n + and M ( n +1)+ has been experimentally demonstrated as a governing factor. , Recently, Gao et al reported two principles for the SOD-like activity of nanomaterials on the basis of their electronic band structures and surface adsorption energies . Transition-metal thiophosphate is a kind of quasi-two-dimensional material connected by metal nodes and thiophosphate linkages, which is of biological significance in regulation of enzyme activity, as well as to mimic the microenvironment of natural SOD containing the metal active site and protein scaffold. , In this study, the transition-metal thiophosphate (M x P y S z ; x = 1–7, y = 1–4, z = 1–29) composed of mixed valence states formed by different bonding states was selected as potential candidates for SOD mimics. Based on the fundamental crystal constants, multiple nanozyme descriptors of 91 M x P y S z were created.…”
mentioning
confidence: 77%
“…25 Transition-metal thiophosphate is a kind of quasitwo-dimensional material connected by metal nodes and thiophosphate linkages, 26−30 which is of biological significance in regulation of enzyme activity, 31 as well as to mimic the microenvironment of natural SOD containing the metal active site and protein scaffold. 32,33 In this study, the transition-metal thiophosphate (M x P y S z ; x = 1−7, y = 1−4, z = 1−29) composed of mixed valence states formed by different bonding states was selected as potential candidates for SOD mimics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Nanozymes, as a new type of nanomaterials with intrinsic enzyme-like catalytic activities, have attracted widespread interest in the past decade, which is attributed to their unparalleled merits such as low cost, high stability, adjustable activities and recyclability that are unmatched by natural enzymes. [6][7][8][9][10][11] In addition, surface modification, such as regulation of the surface charge, hydrophilicity/hydrophobicity and thickness could further diversify the bioactivity of a nanozyme, holding great potential for biosensor construction. 12 Alkaline phosphatase (ALP) is an important enzyme enabling the recognition and dephosphorylation of phosphate esters in living cells, 2,13,14 and therefore mimicking the ALP-like activity will provide new opportunities to construct a span-new sensing platform for phosphorylated biomarkers.…”
mentioning
confidence: 99%